TINJAUAN YURIDIS ASPEK HUKUM DALAM SURAT PERJANJIAN KERJA DITINJAU DARI PERATURAN PRESIDEN NOMOR 70 TAHUN 2012 TENTANG PENGADAAN BARANG DAN JASA DI TANJUNG JABUNG BARAT - Abdul Hariss (Universitas Batanghari Jambi, 2016)
Though the agreement held between the job of chartering public works with private companies have been set up in the book of the law of civil law, but to strengthen and mempertegasnya of the parties making the agreement work.Due to the agreement between the Government of chartering with private parties using State funds that come from the budget of revenue and Expenditure of the country or region using funds derived from Budget revenues and Spending areas, then the provisions of the book of the law of civil law is not enough, so the Government is perceived to add provisions in the agreement which is mandatory for a contractor job, which for the moment are now setting it is set in the presidential regulation Number 70 in 2012 On the procurement of goods and services.With the circumstances mentioned above, then all provisions are made and agreed upon in the agreement must reflect the work, the contractor and includes provisions presidential regulation Number 70 in 2012.Keyword : aspects of the law, the Treaty work, procurement of goods and services